Analisis Kelayakan Usaha Berbasis Hasil Hutan Bukan Kayu Ekosistem Mangrove Di Desa Margasari Lampung Timur - Mayang Haris Wahyukinasih; Christine Wulandari; Susni Herwanti (Department of Forestry, Faculty of Agriculture, University of Lampung, 2014)
Commonly of mangrove forest area in Indonesia has been degraded severely including that lives on East Lampung. It is because of lack conservation applied in as utilization. It needs on home industrial development based on non-timber forest products of mangrove ecosystem in order to reduce the pressure of mangrove area utilization, as has been practiced by some people of Margasari Village. The indicated of the home industries sustainability, however has not been known yet. This research was conducted on April until May 2013 and the aim was to analysize the feasibility of jeruju leaf (Acanthus ilicifus) and pidada fruit (Sonneratia caseolaris) processing business to be some processed product and to analysize the simulation of interest rate and price to determine fiscal policy for business development. The respondent of this research were all of the member of home industry business of Karya Wanita and Peduli Lingkungan Hidup (LPH). The selecting of the respondent was conducted purposively. The method were observation and direct interview whereas the analysis of feasibility which was used was Gross B/C. The result of the research showed that the processing of jeruju leaf (Acanthus ilicifus) and pidada fruit (Sonneratia caseolaris) from 'karya wanita' Group could be conducted because it had Gross B/C score more than 1 that was pangsit and the score was 1.10 and peyek (1.04). For the group of Peduli Lingkungan Hidup (LPH), the good product was peyek (1.42). Gross B/C score more than 1 with 1% interest rate that was peyek (1.09), pempek (1.02), pangsit (1.10), dan sirup (1.009). For the group of Peduli Lingkungan Hidup (PLH), the good product was peyek (1.48). Keywords: gross B/C, home industry, mangrove forest, non-timber forest